(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2023)
Due to consumer demand for recreation and farmers’ need to diversify their income, researchers and policy makers are showing great interest in topics related to agritourism. This study presents a supply-side analysis of agritourism using Taiwan as a case study. Using a sample of 720,148 family farms from the 2010 Agricultural Census Survey in Taiwan, we examine the effects of engaging in agritourism business on farm income, farm inheritance, and family a We determine the impact of these factors on labor supply decisions between on- farm and off-farm. the work. An analytical framework combining a double-robust regression model and semi-parametric estimation is proposed to overcome the endogeneity bias. The results show that participation in agritourism increases farm income and family farm succession. Agritourism farms also have more on-farm family members and fewer off-farm family members than non-agritourism farms. Although agritourism businesses are designed to meet consumer demand for recreation, our results show that they also improve the economic well-being of farms.